STRATEGI MULTIPLE INTELLIGENCES PADA STUDY FROM HOME SEBAGAI INOVASI MENGAJAR GURU SELAMA COVID-19 - Nur Indah Rahmawati; Citra Ayyuhda (Universitas Muhammadiyah Lampung, 2021)
This literature review will discuss the development of challenges or disfficultie for elementary school teachers and students during the Covid-19 Priod in dealing with change incurrent education pattens. The teacher, as the key to successful learning, seeks to increase creativity in teaching. The teacher need to increase creativity and inovasi in dealing with online learning problems. The purpose of research literature is to provide an overview of the creativity a teachers in innovating during the distance learning process. This research uses qualitative methods with literature studies. The results also show that there is a descriptive significant difference between students' Multiple Intelligences ability with the creativity ability and teacher strategy development during learning amidst the implementation of SFH or Study From Home during the Covid-19 pandemic. Intelligence describes the individual's ability to complete tasks to achieve goals.